Bifurculapes Hitchcock 1858: a revision of the ichnogenus - Getty, Patrick Ryan (Atlantic Geoscience, 2017)
Characters differentiating the arthropod trackway Bifurculapes from the similar ichnogenera Lithographus and Copeza include the position, arrangement and orientation of the tracks within the series. Of the five species of Bifurculapes originally described, only Bifurculapes laqueatus and Bifurculapes scolopendroideus are recognized herein; the other three ichnospecies are considered to be nomina dubia or junior subjective synonyms of Bifurculapes laqueatus. Two new specimens, recovered from the Early Jurassic East Berlin Formation of the Hartford Basin in Holyoke, Massachusetts, represent only the second unequivocal occurrence of the ichnogenus outside of the Deerfield Basin. Bifurculapes is currently known only from the Early Jurassic.